Investigating the geothermal energy potential of Absheron region for electricity generation using binary cycle technology - П.Я. Мамедов (Геология и геофизика Юга России, 2024)
Relevance. Geothermal energy offers a clean and sustainable alternative to fossil fuels for electricity and heat generation. This study explores the potential for utilizing geothermal energy alongside existing oil production in the Bibiheybat field, Azerbaijan. The aim of this work is to assess the geothermal energy potential of the Bibiheybat field and evaluate its feasibility for electricity generation. Methods. The study analyzes well flow rates, temperatures, and pressure distributions within the X stratum of the field. Temperature and pressure distribution models are developed using Surfer software. Geothermal energy potential is calculated based on well data and formula application. Binary cycle technology is proposed for electricity conversion. Results. The X stratum exhibits an anticlinal fold structure with varying well depths and temperatures (46-24°C). The geothermal energy potential of the field is estimated at 307,578.56 kWh, with 25,090.15 kWh carried by oil and 282,488.41 kWh by water. Utilizing a binary cycle power plant, approximately 107,652.49 kWh of electrical energy could be generated.